Nasionalisme dalam al-Qur'an (Studi Tematik Terhadap Ayat-ayat Nasionalisme Perspektif Ahmad Musthafa al-Maraghi) - Hidayah , Nurul; Sholeh , Moh. Jufriyadi (Al-Insyiroh: Jurnal Studi Keislaman, 2021)
Nowadays, various ideologies that are pro and contra to nationalism have begun to grow and develop. This nationalism cannot be separated from faith and religion. This is evidenced by the explanation of several verses of the al-Qur'an explicitly discussing nationalism. This study aims to describe the general representative of nationalism according to Ahmad Musthofa al-Maraghi. In this study, using a qualitative approach with the type of literature review, namely by using a thematic method that is descriptive analysis. In collecting data, this research will rely entirely on the interpretation of al-Maraghi by Ahmad Musthofa Al-Maraghi, as the primary source of books, research journals as secondary sources, which are relevant to this research. The results of this study indicate that the general representation of nationalism according to Ahmad musthafa al-Maraghi in (QS. Al-Anbiya; 92), (QS. Al-A'raf: 160), (QS. Al-Baqarah: 144) is a constructive nationalism. spirit of nationalism by upholding all kinds of regulations for the sake of advancing the nation. There are at least three equal principles so that nationalism does not conflict with the Koran and Islamic syaria. Namely nationalism in the form of unity, the grouping of humans based on descent by maintaining their integrity, as well as love for the homeland